2022
DOI: 10.2147/copd.s342357
|View full text |Cite|
|
Sign up to set email alerts
|

Interclass Difference in Pneumonia Risk in COPD Patients Initiating Fixed Dose Inhaled Treatment Containing Extrafine Particle Beclometasone versus Fine Particle Fluticasone

Abstract: Background: Inhaled corticosteroids (ICS) afford therapeutic benefits in some COPD patients, but their widespread use is cautioned due to an increased risk of developing pneumonia. Subclass variations exist, and the risk profile differs for individual ICS. Formulation particle size has been identified as a potential effect modifier. The present study compared the risk of pneumonia among new COPD users of fixed-dose combination inhalers containing fine-particle fluticasone (fp-FDC-F) versus extrafine particle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“… Do fine‐particle fluticasone‐containing ICS formulations have implications in the clinical management of patients with COPD? In real‐life research, patients treated with a fluticasone‐containing ICS formulation were found to have an increased risk of pneumonia, in comparison to patients treated with extrafine beclomethasone 7 . The study's findings emphasize the need for clinicians to be aware of fine‐particle fluticasone‐containing ICS formulations and their different adverse effects when selecting treatments 7 …”
Section: Figurementioning
confidence: 85%
See 3 more Smart Citations
“… Do fine‐particle fluticasone‐containing ICS formulations have implications in the clinical management of patients with COPD? In real‐life research, patients treated with a fluticasone‐containing ICS formulation were found to have an increased risk of pneumonia, in comparison to patients treated with extrafine beclomethasone 7 . The study's findings emphasize the need for clinicians to be aware of fine‐particle fluticasone‐containing ICS formulations and their different adverse effects when selecting treatments 7 …”
Section: Figurementioning
confidence: 85%
“…Much like registries, EMRs and databases such as the Optimum Patient Care Research Database (OPCRD) and Clinical Practice Research Datalink (CPRD) can also add value to the breadth of research on severe asthma and COPD. The OPCRD database has a median follow‐up period of 13 years (with diagnostic information from birth for many patients), offering increased power to study rare adverse events such as pneumonia which RCTs are less able to do 7 . Here are some previously unanswered questions that EMR‐based observational studies have now answered: Does lung function decline more rapidly in asthmatics with more frequent exacerbations?…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…28 In particular, the risk of pneumonia changes with ICS subclass and is lower when using extra-fine ICS at lower ICS doses. [29][30][31] Nonetheless the topic is still subject to debate; a network meta-analysis comparing nine combinations of ICS/LABA/LAMA in COPD found significantly lower pneumonia infections only with the fluticasone propionate (FP)/ glycopyrrolate/salmeterol (SAL). 31 Further evidence on the relationship between distribution to small airways and better clinical control is provided by a recent study specifically assessing the efficacy of an extra-fine formulation of beclomethasone dipropionate/ formoterol fumarate (BDP/FF) 100/6 µg b.i.d in COPD patients with SAD.…”
mentioning
confidence: 99%